Speaking with an accent: Some practical advice for foreign first-time teachers - Berardo, Alfredo Ramiro (2011)
The majority of Ph.D. programs in political science in the United States provide some kind of teaching training for graduate students, which ranges from assisting other instructors to designing and teaching new courses. In most cases, departments make an effort to guide these students in their new role as instructors; however, first-time teachers whose first language is not English do not usually receive any special guidance on how to successfully address the challenge of communicating effectively with their students—an all-too-real problem for many foreign instructors. This article provides some basic tips for improving the communication process that develops in the classroom, and is particularly tailored for individuals whose first language is not English and who are about to take the first steps of their teaching careers.